A review of factors influencing consumer intentions to adopt battery electric vehicles. (October 2017) - Li, Wenbo; Long, Ruyin; Chen, Hong; Geng, Jichao
Abstract: Despite reducing environmental pollution and the excessive consumption of fossil fuels, the number of battery electric vehicles (BEVs) on the road is still low. Why is this so? Why is the mass adoption of BEVs so difficult to realize? One important reason is that the adoption of BEVs is, to a large extent, dependent on the acceptance of private consumers, and their willingness to adopt this mode of transport is insufficient. This study is a systematic overview of peer-reviewed journal articles to identify the reasons for and against consumer intentions to adopt BEVs. A total of 1846 papers were retrieved and after a two-step identification, 40 papers were finally identified and analyzed in detail. The influencing factors were categorized into three main types, namely demographic, situational and psychological, and they were reviewed separately. In addition, the shortcomings and deficiencies in the current studies were also noted.